Methanogenesis and Sulfate Reduction Data from IODP Expedition 370, Nankai Trough Subduction Zone, Japan - Tina Treude; F Beulig; Florian Schubert; Jens Kallmeyer (PANGAEA, 2021)
This dataset contains potential ex-situ microbial methanogenesis and sulfate reduction rates determined with radiotracer techniques (^1?C-bicarbonate and ^3?S-sulfate incubations, respectively) in sediment slurries (sediment mixed with artificial seawater). Minimum biological quantification limit was 0.09 pmol CH? cm?^3 d?^1 and 0.13 pmol SO?^2? cm?^3 d?^1, respectively. Ex-situ incubation temperatures were 40°C for samples from depths ≤360 mbsf, 60°C for for samples from 405–585 mbsf, 80°C for for samples from 604–775 mbsf and 95 °C for for samples from ≥816 mbsf. Methanogenesis samples where amended with hydrogen (130 nmol L?^1). Sulfate Reduction samples where amended with hydrogen (130 nmol L?^1), acetate (5 mmol L?^1), or methane (100% headspace). Incubation times were up to 10 days. For more details on incubation and analytical procedures see related publications.